2020
DOI: 10.1177/1071181320641114
|View full text |Cite
|
Sign up to set email alerts
|

Human-Centered and Psychological Concepts in Undergraduate Engineering Project Documentation

Abstract: The success of engineering and design is facilitated by a working understanding of human thoughts, feelings, and behaviors. In this study, we explored how undergraduate engineering students included such human-centered and psychological concepts in their project documentation. Although, we observed a range of concepts related to design processes, teams, cognition, and motivation, these concepts appeared infrequently and superficially. We discuss how this analysis and approach may help to identify topics that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…One prior investigation observed that psychological concepts were rarely referenced in engineering students’ project documentation (Roscoe, Arnold, & Johnson, 2020). Researchers analyzed over 200 reports from an introductory engineering course wherein students redesigned “the future of being a passenger.” Overall, fewer than 10% of projects mentioned design thinking steps (e.g., empathy, problem-solving, and evaluation; see Dym et al, 2005; Razzouk & Shute, 2012), and fewer than 5% mentioned aspects of teamwork (e.g., consensus and delegation).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One prior investigation observed that psychological concepts were rarely referenced in engineering students’ project documentation (Roscoe, Arnold, & Johnson, 2020). Researchers analyzed over 200 reports from an introductory engineering course wherein students redesigned “the future of being a passenger.” Overall, fewer than 10% of projects mentioned design thinking steps (e.g., empathy, problem-solving, and evaluation; see Dym et al, 2005; Razzouk & Shute, 2012), and fewer than 5% mentioned aspects of teamwork (e.g., consensus and delegation).…”
mentioning
confidence: 99%
“…One prior investigation observed that psychological concepts were rarely referenced in engineering students' project documentation (Roscoe, Arnold, & Johnson, 2020). Researchers analyzed over 200 reports from an introductory engineering course wherein students redesigned "the future of being a passenger."…”
mentioning
confidence: 99%